Efektifitas Pijat Bayi Terhadap Perubahan Kualitas Tidur dan Berat Badan Pada Bayi Lahir Prematur di Klinik Pratama Mitra Subang - Jusmawati, Jusmawati; Widiastuti, Dewi Ayu; Selviyana, Linda (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT The growth and development of premature babies is different from that of full-term babies. The growth and development of premature babies is influenced by various factors including sleep quality and body weight. Massage on the baby will provide stimulation to the body in a sustainable manner, providing a sense of security and comfort to the baby. Babies become relaxed, comfortable, calm, gain weight and sleep well so as to stimulate their growth and development. To analyse the effectiveness of infant massage on changes in sleep quality and weight of premature born babies at Pratama Mitra Subang Clinic. This study used a pre-experimental method with a research design of one group pretes-posttest design involving 60 respondents divided into two groups 30 groups of sleep quality of infants aged 0-6 months and 30 groups of baby weight aged 0-6 months. The research instrument used BISQ questionnaire to measure sleep quality and baby scale (which has been calibrated) for measuring baby weight. Theresults showed that infant massage was effective on changes in sleep quality and changes in body weight of premature infants. The quality of sleep of infants before the majority was sufficient as many as 20 infants (66.7%) after the majority was good as many as 23 infants (76.7%) (p=0.000), while the weight of infants before reat-average 6230 grams and after the average weight of infants 6530 grams (p=0.000). Infant massage is effective in improving the quality of infant sleep and weight gain of infants born prematurely. Keywords: Preterm Infants, Infant Weight Gain, Sleep Quality, Infant Massage.  ABSTRAK Pertumbuhan dan perkembangan bayi prematur berbeda dengan bayi cukup bulan. Pertumbuhan dan perkembangan bayi lahir premature dipengaruhi oleh berbagai faktor diantaranya kualitas tidur dan berat badan. Pijat pada bayi akan memberikan rangsangan pada tubuh secara berkelanjutan, memberikan rasa aman dan nyaman pada bayi. Bayi menjadi rileks, nyaman, tenang, berat badan naik dan tidur pulas sehingga mampu menstimulasi tumbuh kembangnya.Untuk menganalisis efektivitas pijat bayi terhadap perubahan kulaitas tidur dan berat badan bayi lahir prematur di Klinik Pratama Mitra Subang. Penelitian ini menggunakan metode pre eksperimen dengan desain penelitian one group pretes-posttest design dengan melibatkan 60 responden terbagi dalam dua kelompok 30 kelompok kualitas tidur bayi usia 0-6 bulan dan 30 kelompok berat badan bayi usia 0-6 bulan. Instrumen penelitian menggunakan kuesioner BISQ untuk mengukur kualitas tidur dan timbangan baby scale (yang sudah di kalibrasi) untuk pengukuran berat badan bayi.Hasil menunjukkan bahwa pijat bayi terbukti efektif terhadap perubahan kualitas tidur dan perubahan berat badan bayi prematur. Kualitas tidur bayi sebelum mayoritas cukup sebanyak 20 bayi (66,7%) sesudah mayoritas baik sebanyak 23 bayi (76,7%) (p=0,000), sedangkan berat badan bayi sebelum reat-rata 6230 gram dan sesudah ata-rata berat badan bayi 6530 gram (p=0,000).Pijat bayi efektif  terhadap peningkatan kualitas tidur bayi dan kenaikan berat badan bayi lahir prematur. Kata Kunci: Bayi Prematur, Berat Badan Bayi, Kualitas Tidur, Pijat Bayi